Legal Protection for Buyers Who Have Good Faith in Full Payment of Land Rights Without Power of Attorney to Sell from the Perspective of Justice - Siswanto, Moch. Agus (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Research by discussing the problem of how buyers with PPJB made underhand with full payment not followed by a power of attorney to sell get legal protection against the seller's refusal to appear before the PPAT and what legal steps can be taken by buyers in good faith PPJB made underhand with full payment without a power of attorney to sell for the seller's refusal to appear before the PPAT, with the method of statutory regulatory approach and conceptual approach, a conclusion was obtained: Buyers in good faith with PPJB made underhand with full payment without a power of attorney to sell get legal protection against the seller's refusal to appear before the PPAT, but the legal protection is not intended to appear before the PPAT to make a deed of transfer of rights, because in making a deed of transfer, the PPAT is obliged to request the presence of the parties in this case the seller and the buyer or their attorneys. Legal protection for the occurrence of a sale and purchase agreement as referred to in Article 1457 of the Civil Code, each party has reciprocal obligations or achievements, namely the seller promises to hand over the object agreed upon and the buyer has an obligation to pay the price of the goods. Legal efforts that can be taken by a buyer who has good intentions, the PPJB is made underhand with full payment not followed by a deed of power of attorney to sell due to the seller's refusal to appear before the PPAT, that the buyer in fighting for his rights to ownership of the object of sale and purchase, must file a lawsuit with the District Court on the basis of the seller's default and request that the District Court's decision order the PPAT to make a deed of transfer of rights not based on the power of attorney to sell, but based on the court's decision.